Formulation, Development, and Evaluation of Sustained Release Tablet of Ambroxol Hydrochloride - Sonawane, Deepak D. (Asian Journal of Pharmaceutics (AJP), 2022)
Introduction: Ambroxol hydrochloride tablet was formulated as sustained release tablets employing rice bran wax polymer and the sustained release behavior of the fabricated tablets were investigated. Materials and Methods: The objectives of study are Sustained release matrix tablets containing 75 mg ambroxol hydrochloride were developed using different drug polymer ratios of MCC, RBW and DCP. Tablets were prepared by direct compression. Formulation was optimized on the basis of acceptable tablet properties and in vitro drug release and by using 23 factorial designs. Result and Discussion: The resulting formulation produced robust tablets with optimum hardness, consistent weight uniformity and low friability. All tablets but one exhibited gradual and near-completion sustained release for ambroxol hydrochloride, and 98-103% released at the end of 8 h. Conclusion: The results of dissolution studies indicated that formulation F7, the most successful of the study, exhibited drug release pattern very close to theoretical release profile. A decrease in release kinetics of the drug was observed on increasing polymer ratio. Applying exponential equation, all the formulation tablets (except F7) showed diffusion-dominated drug release. The mechanism of drug release from F7 was diffusion with erosion.